x-4/9=-5

Simple and best practice solution for x-4/9=-5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x-4/9=-5 equation:



x-4/9=-5
We move all terms to the left:
x-4/9-(-5)=0
We add all the numbers together, and all the variables
x+5-4/9=0
We multiply all the terms by the denominator
x*9-4+5*9=0
We add all the numbers together, and all the variables
x*9+41=0
Wy multiply elements
9x+41=0
We move all terms containing x to the left, all other terms to the right
9x=-41
x=-41/9
x=-4+5/9

See similar equations:

| Z^2+3*I*z-4=0 | | 9a+7=2a-14 | | 4(2x=5)44 | | 8-5c=-7 | | 6x+3/2=7x+1 | | x+36/6=5 | | 4(2x=5)=44 | | 7x+2/x-3=9 | | x(3+1)=42 | | 3x+50=x+200 | | 2(23)+x=50 | | 29-5v=3v-27 | | 2(3-x)=9+x | | 6x+33=75 | | 23(x+2)=50 | | 5(4b+3)=-25 | | 1(x+3)=42 | | 3.5x-14=8.5 | | x(x+3)=42 | | 7f+12=4f-18 | | 3e+9=42 | | 9b-12=3b+6 | | 2t+2=26 | | /3x+4=2x-4 | | 7r+11=3r-9 | | 15^2x-3=125^x+1 | | n/15-4=-3 | | -3w+17=50 | | 13-1+13=6x | | 4x+3=2x=15 | | 8x+9=−6x−2 | | -2=2/5x-6 |

Equations solver categories